2017
DOI: 10.1042/ebc20160063
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic, adaptive and acquired antimicrobial resistance in Gram-negative bacteria

Abstract: Gram-negative bacteria are responsible for a large proportion of antimicrobial-resistant infections in humans and animals. Among this class of bacteria are also some of the most successful environmental organisms. Part of this success is their adaptability to a variety of different niches, their intrinsic resistance to antimicrobial drugs and their ability to rapidly acquire resistance mechanisms. These mechanisms of resistance are not exclusive and the interplay of several mechanisms causes high levels of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
97
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 88 publications
0
97
0
11
Order By: Relevance
“…The high MIC values shown against Ps. aeruginosa may be due to the overexpression of efflux pumps and the presence of outer membrane permeability barrier in the Gram-negative pathogen, which enhances the outer cell membrane resistance towards antimicrobials as reported previously (Poole et al 1993;Mandsberg et al 2009;Arzanlou et al 2017). Thus, a combination effect of either cinnamon oil or cinnamaldehyde with EDTA was investigated against Ps.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The high MIC values shown against Ps. aeruginosa may be due to the overexpression of efflux pumps and the presence of outer membrane permeability barrier in the Gram-negative pathogen, which enhances the outer cell membrane resistance towards antimicrobials as reported previously (Poole et al 1993;Mandsberg et al 2009;Arzanlou et al 2017). Thus, a combination effect of either cinnamon oil or cinnamaldehyde with EDTA was investigated against Ps.…”
Section: Discussionmentioning
confidence: 57%
“…; Arzanlou et al . ). Thus, a combination effect of either cinnamon oil or cinnamaldehyde with EDTA was investigated against Ps.…”
Section: Discussionmentioning
confidence: 97%
“…Phage predation accounts for a significant proportion of bacterial mortality, up to 80% in some systems ( Rohwer et al, 2009 ), and thus presents a remarkably strong source of selective pressure for bacterial immunity systems. Known bacterial immunity systems can be divided into categories analogous to either intrinsic or acquired antimicrobial resistance systems as denoted by Arzanlou et al (2017) . Indeed, a wide variety of phage defense systems have been found that are analogous to intrinsic mechanisms of antimicrobial resistance, where bacteria constitutively express systems that mediate phage resistance, such as Restriction/Modification systems ( Tock and Dryden, 2005 ), Toxin/Anti-toxin systems ( Dy et al, 2014 ), and the Bacteriophage Exclusion (BREX) system ( Goldfarb et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Effective treatment of bacterial infections is becoming increasingly difficult with the emergence of resistance to multiple classes of antimicrobial drugs. In particular, sepsis due to the multidrug‐resistant (MDR) ESKAPE pathogens ( Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa , and E. coli / Enterobacter species) contribute significantly to morbidity and mortality associated with antimicrobial resistance (700 000 deaths annually) worldwide . Therefore, the discovery and development of new broad‐spectrum antimicrobials with activity against pan‐resistant resistant ESKAPE pathogens causing sepsis is one of the highest global priorities .…”
Section: Introductionmentioning
confidence: 99%